2005
DOI: 10.1090/s0025-5718-05-01778-3
|View full text |Cite
|
Sign up to set email alerts
|

Sharp 𝐿¹ a posteriori error analysis for nonlinear convection-diffusion problems

Abstract: Abstract. We derive sharp L ∞ (L 1 ) a posteriori error estimates for initial boundary value problems of nonlinear convection-diffusion equations of the form ∂u ∂tunder the nondegeneracy assumption A (s) > 0 for any s ∈ R. The problem displays both parabolic and hyperbolic behavior in a way that depends on the solution itself. It is discretized implicitly in time via the method of characteristic and in space via continuous piecewise linear finite elements. The analysis is based on the Kružkov "doubling of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…We use the so-called guaranteed error reduction strategy in [25] and the spatial error estimators proposed in [17]. Our implementation is based on a Matlab adaptive finite element package, AFEM@matlab [26].…”
Section: Adaptive Algorithmmentioning
confidence: 99%
See 3 more Smart Citations
“…We use the so-called guaranteed error reduction strategy in [25] and the spatial error estimators proposed in [17]. Our implementation is based on a Matlab adaptive finite element package, AFEM@matlab [26].…”
Section: Adaptive Algorithmmentioning
confidence: 99%
“…A posteriori error analysis and spatial mesh adaptivity have been applied to the ELM; see [14][15][16][17]. In particular, [16] gave a residual-based L^{L'^) a posteriori error estimator; however, the numerical experiments therein indicated that the norm of the residual on an individual element may be a poor estimate of the local error (the norm of the residual can be used to bound the error on a global basis from above.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These unphysical behaviours can be eliminated considering several approaches (see, for instance [7][8][9][10]14,[16][17][18]22]. The numerical difficulties due to the lack of smoothness when Newton's method is used to solve the algebraic system resulting from the discretization are considered, for example, in [2,4,11,12].…”
Section: Introductionmentioning
confidence: 99%